If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7 + -1x) = 12 (7 * 3 + -1x * 3) = 12 (21 + -3x) = 12 Solving 21 + -3x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -3x = 12 + -21 Combine like terms: 21 + -21 = 0 0 + -3x = 12 + -21 -3x = 12 + -21 Combine like terms: 12 + -21 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 8=-4(3x-4) | | -x-6x+7=42 | | 9-3(x-4)=36 | | -62=5x+3 | | 18+2x/3=16 | | 24=(2x-3) | | 3w-3=4w+8 | | 4(7-x)=4 | | (78+x)+x=434 | | 4.9t^2-13.5t=66 | | 3n=-27 | | 4x^2+18x+14=0 | | -8+6x=38 | | 22x*15*13x= | | 0.6x+3-2x=7x+3 | | 4x-6=6(x+2)+8 | | 9x-4=2x-3 | | 8b+6(-6-2b)=4+b | | x-5+x-5+x-5+x-5=12+x+x | | 2x-3=2(x+4) | | 18(w+3)-45=18+54 | | 25-7a=28+4a | | 5x^4-30x^2= | | 32=5-4a-5a | | 0.02(y-9)+0.20y=0.16y-0.6 | | 2(9s+7)-10s=2(4s+2)-8 | | 18-2x=-36 | | 5w-6+3w=-12 | | -4-3x=17 | | 4+3-939340823094+6-x=-34 | | (5x^2y-2xy^2+3xy-5)(-2x^2y-3xy^2+4xy+7)= | | -4(3x-2)=2x+17 |